PENGARUH MASSAGE EFFLEURAGE TERHADAP PENURUNAN TINGKAT NYERI PADA IBU HAMIL TRIMESTER III DENGAN LOW BACK PAIN (LBP) - Aulya Vira Maylinda, - (2023)
Low Back Pain (LBP) that is not treated quickly and appropriately will get worse and many pregnant women think that low back pain is nothing to worry about. In an effort to reduce low back pain (LBP) experienced by a third of the population of pregnant women, non-pharmacological interventions are given in the form of effleurage massage which has no side effects. The purpose of this study was to determine whether or not there was an effect of effleurage massage on reducing pain levels in third trimester pregnant women with low back pain (LBP). The research design used in this study was a quasy experiment one group pre and posttest on 42 third trimester pregnant women with a total sampling technique. The instruments used included a demographic data questionnaire and a Numeric Rating Scale (NRS) using a paired T-test. The results of this study indicated that there was a significant effect of effleurage massage intervention on reducing pain levels in third trimester pregnant women with low back pain (LBP) of 0.000 (p<0.05).